Controlling: the composition of plasma-activated water by Cu ions. (27th April 2021) - Kutasi, Kinga; Krstulović, Nikša; Jurov, Andrea; Salamon, Krešimir; Popović, Dean; Milošević, Slobodan
Abstract: It is demonstrated that Cu ions can be used to control the ageing of plasma-activated liquids through the Fenton-type reaction, which acts as a competitor to the N O 2 − + H2 O2 + H + → products reaction, and thus moderates the recombination of N O 2 − ions. It is shown that the ageing dynamics is influenced by the type of Cu-ions source used, due to the different ion dissolution dynamics. Using CuNP-colloidal and copper acetate salt solutions, respectively, similar ageing dynamics can be achieved: the lifetime of N O 2 − can be increased to 10 4 min comparing to 10 2 min obtained in plasma-activated water, while the H2 O2 concentration decreases to about half of its initial value. While the treated salt solutions contain the degradation products of the salt compounds, the CuNPs can be filtered out from the plasma-activated colloid (PAC). It is shown that filtration does not influence the concentration of active species, while the ageing of the filtrated PAC depends on the moment of filtration, which determines the concentration of dissolved Cu ions. Using copper foil, the dissolved Cu-ion concentration can be controlled by removing the foil during ageing, and in this way the lifetime of species and the H2 O2 concentration can be adjusted. The effect has been validated in the case of two different plasma sources: a surface-wave microwave discharge and a kHz plasma jet, which produce PALs with different [ N O 2 − ] / [ H 2 O 2 ] concentration ratio, which is the main governor of the ageing process.